An Analysis of Gender-Based Variations in Investment Behavior Regarding Mutual Funds in Nashik City - Tushar K. Savale (Journal of Informatics Education and Research, 2025)
Focusing on mutual funds, the research has considered differences in investment behavior among men and women. The research attempts to determine factors affecting investment decisions through an investigation of differences in demographic characteristics such as age, income, education, and occupation and population characteristics such as investment horizons, risk tolerance, and investment knowledge. With a mixed-method research design employing polls, semi-structured interviews, and secondary data analysis, the study surveys 350 individuals—175 men and 175 women—residents of Nashik. Statistical analysis involves t-tests, Chi-Square testing, Pearson's Correlation Coefficient, and regression analysis to be employed in data analysis.